Optimizing Dryland Crop Management to Regional Climate. Part II: U.S. Southern High Plains Grain Sorghum Production - Mauget, Steven; Kothari, Kritika; Leiker, Gary; Emendack, Yves; Xin, Zhanguo; Hayes, Chad; Ale, Srinivasulu; Louis Baumhardt, R. (Frontiers in Sustainable Food Systems, 2020)
Sorghum's heat and drought tolerance make it, together with upland cotton, one of two crops produced profitably under dryland conditions in the U.S. Southern High Plains (SHP). Here, a simulation-based method evaluates management options that increase median (50th percentile) SHP dryland sorghum yields and estimates those practice's yield risk effects. This method generates climate-representative distributions of grain yields via a crop model driven by weather inputs from 21 SHP weather stations during 2005–2016. Optimal management practices for current SHP climate conditions were sought by generating yield distributions under 32 management options defined by four planting dates, four plant densities, and applied or no applied N. The highest median grain yields resulted from management options with the latest planting date (July 5) and the lowest plant density (24.7 K plants ha−1), while applied N had essentially no yield effect. Increased yields with later planting dates are consistent with sorghum's growth cycle and SHP summer rainfall climatology. Confirming the low plant density yield effect may require additional field studies, as supporting evidence of higher yields at lower densities from other SHP field and modeling studies is inconclusive. These crop simulations, however, suggest late June to early July planting as part of management practices that maximize yields in dryland SHP sorghum production.